Controle estatístico de processo aplicado na uniformidade da irrigação e fertirrigação por gotejamento - Hernández, Ricardo Hernández (2010)
Water use, both to supply the population, as for food production, in increasing numbers, forces countries like Brazil to adopt strict regulations regarding the use of water, which soon will be in effect throughout the Brazilian territory. The drip irrigation systems have increased employment in the face of the above. This thesis aimed to adapt the methodology of statistical process control, widely used in the industry since 1924, to the evaluation process of irrigation and drip fertirrigation, marketed as "drip irrigation kit for household farming". The research was developed at the Experimental Center of Agricultural Engineering - NEEA, State University of West of Paraná - UNIOESTE, in Cascavel, Paraná State, Brazil. Two different systems were settled: an irrigation one and a fertirrigation other, each system was subjected to four treatments (T) according to the variation of hydraulic head (H) applied by gravity, for which we used plastic stents with the capacity of to 200 L, reused from the property. The treatments and their heads identification were as follows: for the irrigation system treatment 1 (T1), H = 12 kPa; treatment 2 (T2), H = 14 kPa; treatment 3 (T3), 16 kPa; treatment 4 ( T4), H = 18kPa; for fertirrigation H = 12 kPa T5, T6 H = 14 kPa, 16 kPa H = T7, T8 = 18kPa. In each treatment were carried out 25 tests on irrigation and 27 ones on fertirrigation, each test was composed of three repetitions, in each repetition the collected volumes of water or fertilizer solution of 40 emitters, 10 seconds on each side line according of the Keller & Karmella Deniculi's methodologies and over a period of four minutes. It was also measured the pressure in the second input (Pinício) and in the fifth lateral line (Pfinal). With these data, flow rates were computed, as well as the Distribution Uniformity (DU), total coefficients of variation (CVt), mean pressure; analyses of descriptive statistics were performed, charts to evaluate the hydraulic performance were elaborated, as well as control charts or Shewhart control charts for DU and CVt. It were applied the ratio of process capability (Cp) and the centrality of process (Cpk) for assessment of uniformity. The statistical analysis, hydraulics, uniformity and statistical process control checked and confirmed that all irrigation tested meets the specifications provided by the manufacturer. The methodology is the beginning of further research for other types of emitters, material manufacturing, culture, and diversity of relief.